Growth and development - VanHeest, J. L. (The science of figure skating, 2018)
Young skaters move through the stages of growth and development in the pattem typical to their peers. Long-term athlete development models work to take advantage of these standard stages. lt is important to understand the models and how they relate to the growth and development pattems described in the current chapter. The development ofbasic motor skills and physical capacities are critical prior to the development of skating-specific skills. An athlete's ability to optimize their training in concert with their stage of development is important in furthering their skating skills over time.